ACCESSOR MINERALS OF RARE METALS IN THE GRORUDITES OF EASTERN AZOV (UKRAINE) - Dubyna, О.; Kryvdik, S.; Belskyy, V.; Vyshnevskyi, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Unlike other Precambrian platforms and shields, alkaline granites and their hypabyssal and effusive variaties in Ukraine have limited distribution. In Eastern Azov region dike analogs of alkaline granites (grorudites) are known. They are different in chemical and mineral composition and considered as analogs of pantellerites (aegirine hihg-Ti) and comendites (amphibole low-Ti). The high-Ti aegirine grorudites are more intensively enriched with incompatible rare elements (REE, Zr, Nb) compared with their low-Ti varieties. Despite the high or elevated concentration of HFSE in grorudites, there are few of their own minerals in these rocks. Thus, in high-Ti grorudites there have been identified such minerals of rare elements as monazite-(Ce), bastnäsite-(Ce), britholite-like mineral and rare earth apatite, zircon and undiagnosed zirconium mineral, whereas only zircon and niobium-containing rutile are diagnosed in amphibole one. These minerals are very small in size, the largest of them can reach 15-20 μm (sometimes up to 50 μm), although most of them do not exceed 10 μm (usually 5-6 μm). It is assumed that a significant part of rare metals are isomorphically included in rock-forming minerals (alkaline pyroxenes and amphiboles), and zirconium minerals, at least part of them, are secondary and formed as result of changing of primary sodium (eudialyte, catapleite, ilerite) or calcium (gittingsite) zirconosilicates which are more typical for peralkaline (agpaitic) rocks. Taking into account the peculiarities of the mineral composition, geochemical features and rare-earth mineralization of the Azov region, there is reason to believe that the HFSE mineralization of these rocks is a consequence of the differentiation of the primary igneous silica unsaturated melt(s). Secondary hydrothermal processes are weakly manifested in the studied rocks and probably presented by replacement of primary accessory minerals. Elevated or high concentrations of Nb in high-Ti grorudites and absence of Nb-minerals may indicate that the PTcondition of differentiation of these rocks (low F concentration, high fO2, and hypabyssal conditions of crystallization) did not contribute to their crystallization. The presence of grorudites in this region increase the prospects of discovering small alkaline granite massifs (holocrystalline analogues of grorudites) to which deposits and/or occurrences of Nb, REE, Zr, Sn, Be can be related.
Keywords: grorudite; zirconium minerals; monazite-(Ce); bastnäsite-(Ce); britholite-like mineral; REE-apatite